THE EFFECT OF GOVERNMENT SUBSIDIES ON THE SUSTAINABILITY OF SMALL TRADERS' BUSINESSES: A STUDY ON TRADITIONAL MARKETS - Dony Hidayat; ThenAdiyatma Taopikul Hadi; Junaidin (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2025)
Small traders often face various challenges in developing their businesses, such as competition from modern retailers, limited capital, low access to technology, and lack of understanding in financial management and business management. This study aims to analyze the effect of government subsidies on the sustainability of small traders' businesses in traditional markets. This study uses a quantitative approach with a sample of 100 people at the Sweta Traditional Market, Mataram, West Nusa Tenggara from February to July 2024 who have received subsidies from the government. Descriptive analysis is used to describe the characteristics of respondents and simple linear regression analysis is used to test the effect of government subsidies on the sustainability of small traders' businesses. The results of the study show that government subsidies have a positive effect on the sustainability of small traders' businesses received (p-value 0.02). Thus, government subsidies have a positive effect on the sustainability of small traders' businesses in traditional markets, especially in increasing profitability and competitiveness